PRODUKTIVITAS CACING SUTRA ( Tubifex sp ) DALAM SUBSTRAT YANG BERBEDA - Abdul Fatah; Andi Rahmad Rahim; Aminin Aminin (Universitas Muhammadiyah Gresik, 2021)
Cultivation of silk worms has not much done by community although the need of silk worm’s cultivation has incresed continuesly time by time. In Fact, the process of cultivation relatively easy and also media for slik worm’s habitat is overfolwing. Therefore, the use of several substrate as media silk worm’s habitat is needed todo. The research was conducted at perum Green Hill Blok B8 for 5 weeks, starts from May until June 2019. This research was aimed to analysing the influence of silidity and the grade of silk worm’s protein after being given some different substrates, by using experimental method and randomized grup designed (RGD) wiht 4 treatments and 3 grup. P1 (control), treatment A (using goat feces), treatment B (using horse feces), treatment C(using cow feces). From those treatments, it can be concluded that different substrat showed a significant effect to absolute weight and the grade of silk worm’s protein. The highest score of absolute weight was resulted from treatment C for 6,7 gram’s and the lowest score was resulted from P1 (control) for 2,9 grams. Mean while. The highest protein content was resulted from treatment C 9,2%. It’s on cow feces